AYURVEDIC MANAGEMENT OF VATARAKTA- A CASE STUDY - Poorva G. Kadam; V.J.Tiwari (International Journal of Ayurveda and Pharma Research, 2020)
Vatarakta is a disease explained in Ayurveda involving Vata Dosha imbalance affecting Rakta Dhatu, where the Vayu gets aggravated due to long distance rides on animals like elephants, camels, horses, and on the other hand Rakta or blood gets vitiated by the consumption of Lavana, Amla, Katu, Kshara etc The Vata, whose passages are blocked by Rakta further undergoes vitiation and further contaminates the Rakta or blood. The blood vitiated by Vayu later burns the whole blood in the body and later gravitates towards the foot. This vicious amalgamation of vitiated Vata and Rakta is called Vatarakta. Vatarakta can even be correlated to Gout on the basis of etiopathology. A 49 years old male patient approached the OPD with the chief complaints of: Right middle finger swelling along with discoloration. Right feet swelling along with burning sensation of b/l sole. Right shoulder joint pain along with difficulty in movements. General weakness was also seen. All the above complains were since 4 months. The patient was given completely Ayurvedic medicines and Panchkarma therapies for 8 days, and later was shifted on only Ayurvedic medicines on discharge and the results were remarkably seen. Hence this study was taken to prove that Ayurvedic management has remarkable results in Vatarakta (Gout). Observation and results were drawn on the basis of assessment criteria. Discussion was done on the basis of entire observations during research. Conclusion was drawn on the basis of result.